National Crime Victimization Survey: School Crime Supplement, 2013 ([Verlag nicht ermittelbar], 2014)
The primary purpose of the School Crime Supplement (SCS) is to obtain additional information about school-related victimizations so that policymakers; academic researchers; practitioners at the federal, state, and local levels; and special interest groups who are concerned with crime in schools can make informed decisions concerning policies and programs. The SCS asks questions related to students' experiences with, and perceptions of crime and safety at school, including preventive measures employed by schools; students' participation in after school activities; students' perception of school rules and enforcement of these rules; the presence of weapons, drugs, alcohol, and gangs in school; student bullying; hate-related incidents; and attitudinal questions relating to the fear of victimization at school. These responses are linked to the National Crime Victimization Survey (NCVS) survey instrument responses for a more complete understanding of the individual student's circumstances.